2021
DOI: 10.3892/br.2021.1410
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of calculated body muscle mass and SARC‑F as methods of screening for sarcopenia in patients with chronic liver disease

Abstract: A simple method is required to screen for sarcopenia in patients with chronic liver disease. In the present study, the value of the existing SARC-F questionnaire as well as calculated body muscle mass (CBMM) approaches were assessed for screening of sarcopenia. A total of 482 patients with chronic liver disease underwent CBMM, grip strength (GS) and SARC-F score assessments. Cross-sectional computed tomography images of the third lumbar vertebrae were analyzed to determine the skeletal muscle (SM) mass in 303 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Our findings also show that the SARC-F item “Strength” independently predicts sarcopenia, and that a SARC-F ≥ 4 is clearly associated with muscle strength rather than muscle mass. These results are consistent with those of previous studies showing that the SARC-F score has a higher correlation with muscle strength but a lower correlation with muscle mass [ 28 , 31 , 32 ]. Muscle strength has many advantages over muscle mass assessed by expensive machines in CLD patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings also show that the SARC-F item “Strength” independently predicts sarcopenia, and that a SARC-F ≥ 4 is clearly associated with muscle strength rather than muscle mass. These results are consistent with those of previous studies showing that the SARC-F score has a higher correlation with muscle strength but a lower correlation with muscle mass [ 28 , 31 , 32 ]. Muscle strength has many advantages over muscle mass assessed by expensive machines in CLD patients.…”
Section: Discussionsupporting
confidence: 93%
“…SARC-F has been reported to show low sensitivity (14–21%) and high specificity (90–94%) for identifying sarcopenia in community-dwelling older adults [ 26 ]. To our knowledge, three studies involving patients with CLD have also shown that the SARC-F has low sensitivity (15–45%) and high specificity (91–98%) in this population [ 17 , 27 , 28 ]. However, the findings of these studies were limited by the small sample size, single center-study design, and the fact that the diagnosis of sarcopenia was not based on the criteria for patients with CLD.…”
Section: Discussionmentioning
confidence: 99%
“…We also utilized HGS for our analyses that is also, however, influenced by the skeletal dimensions of the hand rather than only muscle mass and/or function. 41 Strength measurements of other large muscle groups may be more closely related to functional impairment such as walking or stair climbing 42 and need to be evaluated in future. Our study does not establish the role of FTO expression in vivo in the skeletal muscle of COPD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the cutoff point should be at a point where sensitivity and specificity are optimally balanced, but considering SARC-F's position as a screening tool, better sensitivity may be better [39]. Alternatively, a modified version of SARC-F could be used to increase detection sensitivity for sarcopenia [40].…”
Section: Discussionmentioning
confidence: 99%